- TINJAUAN YURIDIS PELAKSANAAN ALIH STATUS PEGAWAI KOMISI PEMBERANTASAN KORUPSI MENJADI APARATUR SIPIL NEGARA PASCA PUTUSAN MK NOMOR 34/PUU-XIX/2021: - - Navyla Arjinia Putri Widjanarko; Yogo Pamungkas (Reformasi Hukum Trisakti, 2023)
The implementation of the change in employment status of the Corruption Eradication Commission (KPK) employees as Civil Servants is based on Law Number 19 of 2019, which amends Law Number 30 of 2002 concerning the KPK. The formulation of the research problem is: How is the implementation of the change in the status of KPK employees to Civil Servants after the Constitutional Court Decision Number 34/PUU-XIX/2021? And is there any contradiction with the legislation in the implementation of the change in the status of KPK employees to Civil Servants? This research is normative juridical with deductive logical conclusions. The results show that the Constitutional Court Decision states that the implementation of the status change does not violate the 1945 Constitution of the Republic of Indonesia. The transition of KPK's employment status is also a consequence of the institutional status transition of the KPK within the executive branch. The author suggests that the process of changing the status of KPK employees be explained in detail regarding the implementation of the National Insight Test. This is important to avoid the polemic of "weakening the KPK," and legal consequences should be included if KPK employees do not pass the National Insight Test.